2011
DOI: 10.1007/s00424-011-0978-6
|View full text |Cite
|
Sign up to set email alerts
|

Exercise training induces similar elevations in the activity of oxoglutarate dehydrogenase and peak oxygen uptake in the human quadriceps muscle

Abstract: During exercise involving a small muscle mass, peak oxygen uptake is thought to be limited by peripheral factors, such as the degree of oxygen extraction from the blood and/or mitochondrial oxidative capacity. Previously, the maximal activity of the Krebs cycle enzyme oxoglutarate dehydrogenase has been shown to provide a quantitative measure of maximal oxidative metabolism, but it is not known whether the increase in this activity after a period of training reflects the elevation in peak oxygen consumption. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 39 publications
(52 reference statements)
2
21
0
Order By: Relevance
“…Further, Klausen et al (1982) reported an increased a-v O 2 diff of 4% paralleled by a 20-30% increase in oxidative enzyme capacity. However, even if excess activity of citrate synthase compared with in vivo maximal oxygen uptake has been demonstrated in isolated mitochondria from quadriceps muscles (Rasmussen et al 2001), Blomstrand et al (1997Blomstrand et al ( , 2011 found a significant correlation (r = 0.79 and 0.56) also between leg VO 2 and citrate synthase. Taken together, these data indicate that the higher oxidative capacity of the mitochondria is as important as an increased mean transit time for oxygen extraction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, Klausen et al (1982) reported an increased a-v O 2 diff of 4% paralleled by a 20-30% increase in oxidative enzyme capacity. However, even if excess activity of citrate synthase compared with in vivo maximal oxygen uptake has been demonstrated in isolated mitochondria from quadriceps muscles (Rasmussen et al 2001), Blomstrand et al (1997Blomstrand et al ( , 2011 found a significant correlation (r = 0.79 and 0.56) also between leg VO 2 and citrate synthase. Taken together, these data indicate that the higher oxidative capacity of the mitochondria is as important as an increased mean transit time for oxygen extraction.…”
Section: Discussionmentioning
confidence: 99%
“…Capillary density was not evaluated in the present study, but blood flow was increased by 16%, which is identical to the increase found by Klausen et al (1982) after 8 weeks of one-legged training. Interpretation of classical enzyme markers for mitochondrial oxidative capacity remains debated (Tweedie et al 2011), andBlomstrand et al (2011) found only oxoglutarate dehydrogenase to provide a quantitative measure of the oxidative capacity of the muscles. However, Klausen et al (1981Klausen et al ( , 1982 reported a 20% increase in muscle capillarization following one-legged training indicating an almost unchanged mean transit time.…”
Section: Discussionmentioning
confidence: 99%
“…Cross‐sectional studies in humans indicate that endurance trained muscles may have a 30–60% higher peak hyperaemic responses to exercise than untrained muscles (Andersen & Saltin, 1985; Snell et al 1987; Richardson et al 1993). There are few longitudinal studies in humans where the effect of training on peak exercise muscle hyperaemia has been examined (Juel et al 2004; Mourtzakis et al 2004; Blomstrand et al 2011). Blomstrand et al (2011) studied 14 recreationally active subjects who performed one‐legged knee extension exercise for 5–7 weeks, 3–5 days per week (∼1 h per session), while the other leg remained untrained (Fig.…”
Section: Muscle Fibre Type Training and Reduced Physical Activitymentioning
confidence: 99%
“…There are few longitudinal studies in humans where the effect of training on peak exercise muscle hyperaemia has been examined (Juel et al 2004; Mourtzakis et al 2004; Blomstrand et al 2011). Blomstrand et al (2011) studied 14 recreationally active subjects who performed one‐legged knee extension exercise for 5–7 weeks, 3–5 days per week (∼1 h per session), while the other leg remained untrained (Fig. 3).…”
Section: Muscle Fibre Type Training and Reduced Physical Activitymentioning
confidence: 99%
See 1 more Smart Citation